Federal fiscal policy and aggregate demand, 1956-66 - Junz,Helen B (Washinton,D.C : Board of Governors of the Federal Reserve System, 1967)
This paper reviews and attempts to evaluate the effects of fiscal policy actions,discretionary and unplanned , in regard to stated policy goals and longer term-term objectives
obn 22/01/2019
Loans
Keywords: Fiscal policy -- United States; United states -Economic conditions-1945-; Economic history